Development of new products using APQP and quality gates - Dourado, João Paulo (2015)
Reducing time-to-market is the main goal of most companies, to enter the market sooner, build market share and maximize return on their investments. The use of concurrent engineering, Advanced Product Quality Planning (APQP) and quality gates are important in the New Product Development (NPD) process, but it is important to focus in the points on where the tools are not flexible and reinforce the process. The main focus of this work reveals that concurrent tasks between customers and suppliers cause most of the delays in production and are the basis for further work. Methodologies and tools to reduce time-to-market are presented and discussed. Conclusions are drawn that suggest improvements regarding concurrent engineering approaches and their critical issues. Major bottlenecks are presented based on the revised literature.